Prevalence of Trichomonas vaginalis Among Married and Single Sexually Active Females in Oguta LGA, Imo State, Nigeria - Kamalu, Nkiru Anastesia; Kamalu, Chiamaka Sandra; Egbe, Chinonyerem Udoaku; lhejirika, Uchechi Daureen Gift; Asianuba, Rita; Anukam, Uzuma Stella (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2025)
Trichomonas vaginalis is one of the most common non-viral sexually transmitted infections globally. It is mostly attributed in females by a frothy-greenish yellow foul odour vagina discharge accompanied with vulva vaginal irritation, dyrusia and lower abdominal pains. Trichomonas is linked to increased mortality as well as a predisposing factor to HIV infections and cervical cancers. This study was conducted to determine the prevalence of Trichomonas vaginalis. infection among females in Ohaji Egbema, Ogut, Local Government Area. Imo State, Nigeria. Using vaginal swaps and urine samples, a total of 104 females between the ages of (14-43) years were examined. An overall prevalence of females within the age bracket of (24-28) years recorded the highest number of infections while no infections were recorded among the females between the age bracket of (14-18) years, the variation between singles and married was monitored and it was observed that married females had lower prevalence of this infection. There is a need for public health enlightening of adolescents, young female adults, including the elderly by religious organizations, relevant governmental and non-governmental agencies on sex education, public health implication of this infection and also the need to use protection or abstain from sex. Sexually active females should also be taught on how to practice monogamy.